Síntese e atividade fitotóxica de 2-fenil-6,7-exo-isopropilidenodioxi-8-oxabiciclo [3.2.1]oct-2-eno Synthesis and phytotoxic activity of 2-Phenyl-6,7-exo isopropylidenedioxi-8-oxabicyclo[3.2.1]oct-2-ene - Luiz Cláudio A. Barbosa; Antônio J. Demuner; Adilson V. Costa; Eduardo E. L. Borges; John Mann (Química Nova, 2000)
The [3+4] cycloaddition between furan and the oxyallyl cation generated from 1-bromo-1-phenylpropan-2-one (4), resulted in the formation of 2-phenyl-8-oxabicyclo[3.2.1]oct-6-en-3-one (5) in 30% yield. This compound was further converted into 2-phenyl-6,7-exo-isopropylidenedioxi-8-oxabicyclo[3.2.1]oct-2-ene (13) in 35.4% yield. The selective effect of compound (13) and its isomer 3-phenyl-6,7-exo-isopropylidenedioxi-8-oxabicyclo[3.2.1]oct -2-ene (1a) on the radicle growth of Sorghum bicolor L. (sorghum) and Cucumis sativus L. (cucumber) were evaluated. For both plants, compound 13 showed to be more potent than its isomer 1a.